Dynamic methods in teaching geometry at different levels - Árki, Tamás; Krisztin Német, István (Teaching Mathematics and Computer Science, 2004)
In this paper we summarize and illustrate our experiences on DGS-aided teaching geometry of the courses "Computer in mathematics" and "Mathematical software" held for students at Juhász Gyula Teacher Training College of University of Szeged. Furthermore, we show examples from our grammar school experiences too. The figures in this paper were made by using Cinderella ([19]) and Euklides ([21]).